PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF THE DEVELOPING MOTIVATION FOR SPORTS ACTIVITIES AMONG STUDENTS - Arzimbetov, Tileubergen Tilepbergenovish (SCIENCE and SOCIETY, 2026)
The article examines the pedagogical and psychological characteristics of developing students’ motivation for sports activities from theoretical and practical perspectives. The study reveals the essence, structure, and formation factors of sports motivation, as well as its role in the physical, psychological, and social development of students. Special attention is given to pedagogical approaches, psychological mechanisms, motivational strategies, and the influence of the educational environment on increasing students’ interest in sports activities. The research findings indicate that the balanced development of intrinsic and extrinsic motivation contributes to enhancing students’ academic engagement and sports participation.